Organic Mosquito Patch: The Use of Lemongrass, Garlic and Marigold - Nathalie Faith Biñas; Ella Mae Cuba; Cholo Anthony Gargarita; Ameer Jordan Minsu; Amera Malaco (Universitas Pendidikan Indonesia (UPI), 2021)
This study aims to determine the possibility of organic mosquito patches as an alternative to mosquito repellents. The results showed that the control group, namely commercial mosquito patches, was able to obtain the highest rate of repelling mosquitoes. However, statistical analysis did not show a significant difference in the three patches. Thus, the manufacture of organic mosquito patches is as effective as commercial mosquito patches at repelling mosquitoes. In addition, organic mosquito patches have the most economical product compared to commercialized patches. Thus, making organic mosquito patches is not only as effective as commercial mosquito patches but also much more affordable than they cost. It is recommended to use an organic mosquito patch as an alternative to mosquito repellent.